Meta Analysis the Effect of Cadmium Exposure on Chronic Renal Filure in Adults - Zahra, Fathia Mutiara; Rahardjo, Setyo Sri; Murti, Bhisma (Indonesian Journal of Medicine, 2022)
Background: Heavy metals, such as cadmium, are heavy metals that are hazardous to health. Chronic exposure to cadmium is associated with decreased glomerular filtration rate and increased risk of chronic renal failure. This study was conducted to determine how much influence cadmium exposure has on the incidence of chronic kidney failure in adults. The purpose of this study was to analyze the effect of cadmium exposure on the incidence of chronic kidney failure in adults.Subject and Method: This study is a systematic review and meta-analysis using the PRISMA flowchart with PICO as follows, Population: Adults. Intervention: Exposure to Cadmium. Comparison: No Cadmium Exposure. Outcome: Chronic Renal Failure. Search articles using several databases including PubMed, Google Scholar, and Science Direct with the search keywords “adults” AND “cadmium exposure” AND “chronic kidney failure”. The articles submitted ranged from 2013 to 2021. Analysis was performed using RevMan 5.3 as a statistical program.Results: There are 11 articles, originating from the continents of Asia and Europe. The results of the meta-analysis showed that exposure to cadmium increased the risk of developing chronic renal failure in adults by 2.81 times compared with adults who were not exposed to cadmium and was statistically significant (aOR = 2.81; 95% CI = 1.74 to 4.51; p < 0.001).Conclusion: Cadmium exposure may increase the risk of chronic kidney failure in adults.Keywords: cadmium, chronic renal failure, adultsCorrespondence: Fathia Mutiara Zahra. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: efemzahra31@student.uns.ac.id. Mobile: +62 815-6798-7661.Indonesian Journal of Medicine (2022), 07(01): 61-72https://doi.org/10.26911/theijmed.2022.07.01.07